Diseño, construcción y análisis de eficiencia de seguidores solares a un eje y dos ejes con fines de generación fotovoltaica - Medina Sánchez., Johan Alexander (2022)
In this research work, two automatically controlled solar tracking systems (one axis and two axes) were designed, built, and analyzed through an experimental study in order to estimate the highest solar power output economically in a 10 W photovoltaic solar panel according to the direction of propagation of the solar radiation beam from sunrise to sunset. The tracking systems will be located in the southern region of Ecuador in the city of Loja. The designed tracking systems consist of photoresistors that will act as light intensity measurement sensors, an Arduino programming board that will control the servomotors with an algorithm created to position the solar panel of the system based on the information from the input sensors, keeping the solar panel perpendicular to the sun's rays. The designed algorithm contains a section to communicate the Arduino board with a data acquisition tool software for Microsoft Excel, allowing real-time monitoring with easy spreadsheet analysis of the data collected from the current sensors of each photovoltaic solar panel. The experiment was carried out over a two-week period: during the first week, the researcher verified the effectiveness of the established algorithm, as well as the correct calibration of the electronic components. For the second week, the researcher collected official data that would aid him to identify the efficiency of the tracking systems. To analyze the efficiency of the solar tracking systems, a statistical comparison of the stored current data was made, thus evaluating their performance in the Southern Region of Ecuador, with a 33% and 59% increase in energy with the use of single-axis and dual-axis systems accordingly. Keywords: Photovoltaic, solar tracker, one-axis tracker, two-axis tracker, arduino, sun movement.